(untitled) (Global Journal of Medical Research, 2015)
Induction of global organ disease has become important with the events related to diabetes in both the developed and developing world. Type 2 diabetes and peripheral organ disease are connected to Type 3 diabetes that involves the brain early in life associated with brain diseases (stroke, dementia, Alzheimer’s disease).The incidence of diabetes has been predicted to increase to 21% by 2050. In various continents the rise in the global diabetes epidemic has been associated with diseases of various organ diseases related to obesity, diabetes and neurodegenerative diseases (Parkinson’s disease and Alzheimer’s disease). Nutritional therapy has become of central importance as early nutritional therapy may delay organ disease and aging.